An informative search of dyes content rhodamin b in blusher, lipstick, and eyeshadow cosmetics - Haryati, Husnul; Guntarti, Any (Universitas Ahmad Dahlan, 2022)
Decorative cosmetics are preparations used to beautify the appearance and cover up flaws in the skin, such as blemishes on the skin so that the user looks fresher. Examples of decorative cosmetics include lipstick, blusher, eye shadow, and so on, which are usually given the addition of synthetic dyes such as rhodamine. The addition of rhodamine B dye to cosmetics is not permitted. However, the use of dyes is still widely abused by irresponsible people. This review article aims to see whether Rhodamine B dye is present in decorative cosmetics such as blusher, lipstick, and eye shadow. I am writing review articles by searching using search engine assistance, namely Google Scholar, PubMed, and Science Direct. A literature search was performed using the following keywords or terms and strategies: